"A Pain in the Neck" - Ernest Wang; John Vozenilek (Association of American Medical Colleges, 2009)
Abstract There are several critical issues related to difficult airway management that medical students and emergency medicine residents should understand, including recognizing a difficult airway; knowing when a difficult airway is contraindicated or relatively contraindicated to paralyze a patient with an expanding neck mass; and understanding their difficult airway adjuncts and whether they have an algorithmic approach to this process. To help with this, learners were presented this high-fidelity simulation case of a 64-year-old female who presents via emergency medical services with a chief complaint of "trouble breathing" and swelling in the neck. Initial vital signs are stable. The condition progresses to acute respiratory distress secondary to progressive expansion of neck mass shortly after arrival. Anesthesia/ENT consultants are unavailable. The learner must proceed to intubation of the difficult airway. The case presents a rare presentation of an expanding neck mass secondary to a ruptured inferior thyroid artery aneurysm. The patient subsequently deteriorates and requires definitive airway management. This publication includes the lab values and X-rays needed to replicate the case as well as an evaluation sheet based on ACGME competencies. To simulation the neck mass on the mannequin we place a sponge or rolled up latex glove, and this seems to add realism to what the learner visualizes. Other than a standard high-fidelity simulator set up, you will need difficult airway equipment, and an extra monitor or computer to show the radiographic stimuli. This case presents an opportunity for medical students and emergency medicine residents to experience a true difficult airway and allows them to practice a difficult airway algorithm as well as life-saving, time-sensitive airway procedures without putting the patient at risk.